2011
DOI: 10.1016/j.ejpain.2011.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Successful pain relief in non‐responders to spinal cord stimulation: The combined use of ketamine and spinal cord stimulation

Abstract: Although spinal cord stimulation (SCS) is an established therapy for chronic neuropathic pain, still 30% of patients do not respond adequately to trial stimulation. These so called "non-responders" do not receive a permanent implantation for pain relief. The induction and maintenance of central sensitization plays a pivotal role in (chronic) neuropathic pain and is thought to be the resultant of the activation of the N-methyl-d-aspartate (NMDA) receptor in the dorsal horn. Blocking the NMDA receptor through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 45 publications
3
31
0
1
Order By: Relevance
“…This incremental efficacy upon repetitive SCS is consistent with, but more marked than, observations in previous reports (Maeda et al, 2008;Yang et al, 2011;Shechter et al, 2013). In our previous work, which used 50 Hz monopolar stimulation over a longer 30 min period (Smits et al, 2006), the acute anti-hyperalgesic effect largely reversed within 1 h. However, when SCS was applied early after pSNL, the effect was longer lasting than in established (16 day) pSNL animals (Truin et al, 2011a). The milder sub-maximal stimulus parameters used here in conjunction with the relatively earlier SCS intervention, 3 days following nerve injury may make it easier to evoke long-lasting and incremental SCSinduced reversal of hyperalgesia.…”
Section: Figuresupporting
confidence: 91%
“…This incremental efficacy upon repetitive SCS is consistent with, but more marked than, observations in previous reports (Maeda et al, 2008;Yang et al, 2011;Shechter et al, 2013). In our previous work, which used 50 Hz monopolar stimulation over a longer 30 min period (Smits et al, 2006), the acute anti-hyperalgesic effect largely reversed within 1 h. However, when SCS was applied early after pSNL, the effect was longer lasting than in established (16 day) pSNL animals (Truin et al, 2011a). The milder sub-maximal stimulus parameters used here in conjunction with the relatively earlier SCS intervention, 3 days following nerve injury may make it easier to evoke long-lasting and incremental SCSinduced reversal of hyperalgesia.…”
Section: Figuresupporting
confidence: 91%
“…The results in Figure include animals that were considered responders to SCS, which accounted for 10 out of 16 animals (∼63%) randomized into the SNI + SCS on group. This percentage is congruent with previous reports, which also have discussed criteria to distinguish a responder from a nonresponder . Animals considered SCS responders were those with a paw withdrawal score equivalent to 40% of the average baseline score after 72 hours of stimulation.…”
Section: Discussionsupporting
confidence: 90%
“…SCS is generally delivered both clinically and in experimental studies below motor threshold [33,38,66,76] and the majority of these use intesnities around 2/3 of motor threshold to produce analgesia [32,89]. The current study showed that intensities at 75% of motor threshold were less effective than 90% and 50% had no effect.…”
Section: Discussionmentioning
confidence: 65%